Penggunaan Metode Fitrah Berbasis Multimedia dalam Pembelajaran Bahasa Arab - Ii Rahmanudin; Burhan Lukman Syah (INAIFAS PRESS, 2022)
The Arabic learning method continues to develop until it gives rise to the Fitrah method which has been applied at SMA Al-Azhar 24 Islamic Boarding School Bandung. This study conducted to analyze the Fitrah method at the institution which was applied to class X. This study used descriptive qualitative method with a phenomenological approach to describe and analyze every phenomenon that occurs in learning Arabic. The results of this study indicated that the application of the Fitrah method at Al-Azhar 24 Islamic Boarding School made learning Arabic more active and communicative. There was an increase of 29% from the previous one who did not use the Fitrah method with their multimedia devices. This method in addition having its own characteristics, there are also similarities with previously popular methods.